528PHigh-biologically effective dose radiotherapy may improve local control of small cell lung cancer patients with brain metastases: A propensity-matching analysis. (24th November 2019) - Zhuang, Q; Lin, F; Lin, X; Li, J; Junxin, W
Abstract: Background: To compare the effects of high biologically effective dose (BED) and low BED radiotherapy for small cell lung cancer (SCLC) with brain metastases (BMs), and identify the prognostic factors of survival. Methods: A total of 250 consecutive limited-stage (LC) SCLC with BMs patients in our institution were retrospectively analyzed, from January 1998 to June 2018. Preliminary screening of the prognostic factors was accomplished by Kaplan-Meier univariate analysis. Baseline covariates were balanced by a propensity-matching analysis. And survival curves between two groups were compared by log-rank test. The Cox regression model was used to analyze factors associated with prognosis. Results: The Cutoff Finder program exported an optimal BED cutoff value of 47 for all patients. The high-BED (>47 Gy) group had a significantly better brain metastases progression-free survival (BMPFS) than low-BED (≤47 Gy) group (median BMPFS: 14.4 vs. 8.3, P < 0.001). Multivariate analysis found that BED, smoking and age (P < 0.001) were independently prognostic factors affecting BMPFS. And after 1:2 propensity score matching, 176 patients were divided into the high-BED group (n = 59) and the low-BED group (n = 117). In the matched cohort, BMPFS was significantly higher in the high-BED group than low-BED group (P < 0.001). Conclusions: BED, smoking and age were observed to affect BMPFS of SCLC patients with BMs. High BED radiotherapy (>47 Gy) might improve local control. Additional study is warranted. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.